The basic systematisation of macromolecular compounds - Čatić, Igor (Array, 2011)
The word polymers is usually related to plastics and rubber. This definition narrows down the meaning of the word to a very significant group of materials, but leaves out numerous other substances and materials that are also polymers. The consequence is the difficulty in observing the interconnection or comparability of polymers among each other or with other non-polymeric substances and materials. Therefore, a proposal of the basic systematisation of macromolecular compounds has been elaborated. We came to the conclusion that we have to change paradigm of classification of materials. For a very long time the usual classification of materials was the division in two main groups, metals and non-metals. According to the quantity and importance of materials we are proposing a new division, into polymers and non- polymers. The inorganic and organic plastics and vulcanised rubbers are just peak polymers. Particular attention is paid to the systematisation of composed materials and composed products. Attention is also paid to make clear that all plastics and rubber are manmade, including bioplastics.